Feeding citrus pomace fermented with combined probiotics improves growth performance, meat quality, fatty acid profile, and antioxidant capacity in yellow-feathered broilers - Liu, Yanchen; Tang, Yantian; Mei, Huadi; Liu, Zhichang; Li, Zhenming; Ma, Xianyong; Luo, Zhihui; Huang, Weiwen; Li, Yuanfei; Yu, Miao (Frontiers in Veterinary Science, 2024)
IntroductionThe reasonable and efficient utilization of agricultural by-products as animal feed has the capacity to not only mitigate the scarcity of conventional feedstuff but also alleviate the environmental load. This study was aimed to investigate the effects of feeding citrus pomace (CP) fermented with combined probiotics on growth performance, carcass traits, meat quality and antioxidant capacity in yellow-feathered broilers.MethodsA cohort of 540 female yellow-feathered broilers (Qingyuan partridge chicken, 90-day-old) were randomly divided into three groups and, respectively, fed the basal diet (Control), diet containing 10% unfermented CP (UFCP) and diet containing 10% fermented CP (FCP).ResultsThe results showed that dietary FCP significantly increased (p < 0.05) the final-body-weight and average-daily-gain of broilers, and the pH45 min and b*24 h values in breast muscle, while tendentiously lowering the feed-to-gain ratio (p = 0.076). The levels of inosine monophosphate (p < 0.05) and intramuscular fat (p = 0.083) in the FCP group were higher than those in the control group. Remarkably, dietary FCP and UFCP increased the levels of polyunsaturated fatty acids (PUFAs) and n-6 PUFAs (p < 0.05). Moreover, dietary FCP decreased (p < 0.05) the malondialdehyde content and increased (p < 0.05) the glutathione peroxidase content in serum. Ingestion of FCP and UFCP increased the levels of total antioxidant capacity and catalase activity in serum, and concentrations of glutathione peroxidase and catalase in breast muscle (p < 0.05). Additionally, diet containing FCP or UFCP upregulated the expression of SREBP − 1c, FAS, NRF2, GSH-Px, and CAT in breast muscle (p < 0.05).DiscussionOverall, dietary supplementation with FCP obviously improved meat quality, enhanced the antioxidant capacity and regulated the lipid metabolism, contributing to the improvement of growth performance of yellow-feathered broilers.